Composition for sealant and application of composition in heat insulation glass
By using silanized (p-methyl)styrene-isobutylene copolymer, thermoplastic elastomer and tackifier composition, the existing sealant has been solved, and the problem of slow curing and insufficient binding force in the manufacture of hollow glass is achieved, and the sealant is quickly cured and efficiently bonded, which is suitable for the manufacture of hollow glass.
Patent Information
- Application Number
- CN202311152036.7
- Authority / Receiving Office
- CN · China
- Patent Type
- Applications(China)
- Current Assignee / Owner
- Filing Date
- 2023-09-07
- Publication Date
- 2025-03-11
AI Technical Summary
The existing sealants have problems such as slow curing, insufficient binding force and sensitivity to ambient temperature in the manufacturing of hollow glass, which is difficult to meet the demand for sealants in hollow glass manufacturing.
A sealant composition is adopted, including a silanized (p-methyl)styrene-isobutylene copolymer, a thermoplastic elastomer and a tackifier. The silanized copolymer reacts with water during use to improve adhesion and airtightness.
It realizes rapid curing of sealant, improves bonding strength and airtightness, meets the needs of hollow glass manufacturing, and has good solvent resistance, heat resistance and low temperature characteristics.
Smart Images

Figure BDA0004437380160000101 
Figure BDA0004437380160000111
Abstract
Description
Technical Field
[0001] The invention belongs to the technical field of thermal insulation glass and relates to a sealant composition and application thereof in thermal insulation glass. Background Art
[0002] Insulating glass units typically include a pair of glass sheets held at a fixed distance from each other by a spacing structure (spacer) and a sealing structure, wherein the sealing structure extends around the inner surfaces of the glass sheets to define a sealed and insulated space between the glass sheets. In an insulating sash assembly, the spacer is an integral part of the sash frame, and the glass sheets are connected to the spacer by a sealant or adhesive composition. The sealant or adhesive composition can also be used to seal the edges of the insulating glass assembly to provide a barrier to prevent moisture from penetrating into the interior of the assembly and to prevent insulating gases (such as argon) from leaving the air chamber.
[0003] Chemically cured thermosetting compositions and hot melt butyl compositions are two types of sealants commonly used in the insulating glass industry. Chemically cured systems include liquid polysulfide rubber, polyurethane, mercaptan-modified polyether polyurethane and two-component siloxane. Hot melt butyl polymers are also called "non-curing system" sealants.
[0004] Thermosetting compositions are usually two-component systems, and the components are only mixed at room temperature when used. They cure slowly, increasing production difficulty and cost. Hot-melt butyl compositions usually solidify quickly, but are greatly affected by ambient temperature. They soften easily at high temperatures and harden at low temperatures, and their final bonding strength is weak.
[0005] Other sealant compositions that have been developed include one-component sealants such as thermoplastic hot melt adhesives and air-curing resins that polymerize upon exposure to ambient atmosphere. Such sealants have the property of forming tension when bonding two dissimilar substrates.
[0006] The sealant for insulating glass requires not only suitable base coating viscosity during manufacturing, easy coating and providing a certain initial bonding strength, but also good bonding strength and airtightness of the finished product. There has always been a strong demand for such a suitable sealant in the manufacture of insulating glass. Summary of the invention
[0007] In order to solve the above technical problems, the present invention provides the following technical solutions:
[0008] A sealant composition, comprising at least:
[0009] Silylated (p-methyl) styrene-isobutylene copolymer 5-80wt%;
[0010] Thermoplastic elastomer 1-75wt%; and
[0011] Tackifier 5-60wt%.
[0012] According to an embodiment of the present invention, the grafting rate of silane groups in the silylated (p-methyl)styrene-isobutylene copolymer is 0.1 to 20 mol%. In the present invention, the grafting rate refers to the molar number of silane groups per 100 moles of copolymer molecules. Specifically, the grafting rate is, for example, 1 mol%, 2 mol%, 3 mol%, 4 mol%, 5 mol%, 6 mol%, 7 mol%, 8 mol%, 9 mol%, 10 mol%, 15 mol%.
[0013] According to an embodiment of the present invention, the silylated (p-methyl)styrene-isobutylene copolymer has moisture curability, that is, during actual use, specifically when used as a sealant for insulating glass, the silylated (p-methyl)styrene-isobutylene copolymer undergoes cross-linking after the silane groups in the silylated (p-methyl)styrene-isobutylene copolymer react with water, thereby increasing the adhesion and airtightness of the sealant.
[0014] According to an embodiment of the present invention, the silylated (p-methyl)styrene-isobutylene copolymer is selected from at least one of the reactants of a (p-methyl)styrene-isobutylene copolymer and a silane of the general formula RR′SiY2;
[0015] In the general formula of the silane RR′SiY2, R is selected from a monovalent olefinic unsaturated hydrocarbon or a hydrocarbyl group that can react with a free radical point generated on the main chain of the isobutylene copolymer; when R is selected from a hydrocarbyl group, it is not hydrolyzable;
[0016] R′ is selected from alkyl, aryl or Y;
[0017] Y is selected from hydrolyzable organic groups.
[0018] According to an embodiment of the present invention, in the general formula, R may be selected from vinyl, allyl, butenyl, 4-pentenyl, 5-hexenyl, cyclohexenyl or cyclopentadienyl; preferably, R is selected from vinyl.
[0019] According to an embodiment of the present invention, in the general formula, Y can be selected from at least one or two or more of an alkoxy group (for example, a C1-C4 alkoxy group), an acyloxy group, an oxime group (oximo), and a substituted amino group. Further, the C1-C4 alkoxy group is selected from at least one or two or more of a methoxy group, an ethoxy group, or a butoxy group. Further, the acyloxy group is selected from, for example, a formyloxy group, an acetoxy group, or a propionyloxy group. Further, the oxime group (oximo) is selected from, for example, -ON=C(CH3)2, -ON=C(CH3)(C2H5), and -ON=C(C6H5)2. Further, the substituted amino group is selected from, for example, an alkylamino group or an arylamino group, such as -NHCH3, -NHC2H5, and -NHC6H5.
[0020] According to an embodiment of the present invention, in the general formula, R' represents an alkyl group, an aryl group or Y. For example, R' is selected from a methyl group, an ethyl group, a propyl group, a butyl group, a phenyl group, an alkylphenyl group or Y. Further, R' is preferably a methyl group or an alkoxy group. Specifically, the alkoxy group can be selected from a C1-C4 alkoxy group; further, the C1-C4 alkoxy group is selected from, for example, at least one or two or more of a methoxy group, an ethoxy group or a butoxy group.
[0021] According to a preferred embodiment of the present invention, in the general formula of the silane, R is selected from a vinyl group, R' is selected from a methyl group or a Y group, and Y is selected from an alkoxy group (such as an ethoxy group or a methoxy group).
[0022] According to a preferred embodiment of the present invention, the silane is at least one selected from vinyltriethoxysilane, vinyltrimethoxysilane and methylvinyldimethoxysilane.
[0023] According to an embodiment of the present invention, the number average molecular weight of the silylated (p-methyl)styrene-isobutylene copolymer is 2000-1000000, preferably 10000-500000, more preferably 10000-50000, for example, 10000, 100000, 200000, 300000, 400000, 500000, 600000, 700000, 800000, 900000.
[0024] According to an embodiment of the present invention, in the composition, the content of the silylated (p-methyl)styrene-isobutylene copolymer is, for example, 10 wt%, 20 wt%, 30 wt%, 40 wt%, 50 wt%, 60 wt%, or 70 wt%.
[0025] According to an embodiment of the present invention, the composition further contains 5-50 wt% of amorphous poly-α-olefin, for example, 10 wt%, 20 wt%, 30 wt%, 40 wt%.
[0026] According to an embodiment of the present invention, the amorphous poly alpha-olefin refers to an amorphous homopolymer and / or copolymer of monomers such as ethylene, propylene, 1-butene, 1-pentene, 3-methyl-1-butene, 1-hexene, 3-methyl-1-pentene, 4-methyl-1-pentene, 3-ethyl-1-pentene, 1-octene, 1-decene, 1-undecene, etc. Preferably, the amorphous poly alpha-olefin is selected from at least one of random polypropylene, propylene / ethylene amorphous copolymer, propylene / 1-butene amorphous copolymer, and ethylene / propylene / 1-butene terpolymer amorphous copolymer. Also exemplary, the amorphous poly alpha-olefin is selected from ethylene / propylene / 1-butene terpolymer amorphous copolymer (APAO), such as APAO obtained by catalytic copolymerization of 10-15wt% ethylene, 55-60%wt propylene and 25-30wt% 1-butene mixed monomers.
[0027] According to an embodiment of the present invention, the number average molecular weight of the amorphous poly-α-olefin is 5000-100000, for example, 6000, 10000, 19000, 50000, 80000, or 90000.
[0028] Exemplarily, the amorphous poly-α-olefin is preferably an ethylene / propylene / 1-butene terpolymer (APAO), such as VESTOPLAST508 (Evonik).
[0029] According to an embodiment of the present invention, in the composition, the content of the amorphous poly-α-olefin is, for example, 10 wt%, 20 wt%, 30 wt%, 40 wt%, or 50 wt%.
[0030] According to an embodiment of the present invention, the thermoplastic elastomer is selected from at least one of polyisobutylene, isobutylene copolymer, ethylene-propylene rubber, butadiene and styrene block copolymer, isoprene and styrene block copolymer, ethylene vinyl acetate, random polypropylene, ethylene acrylate (methyl) copolymer, etc., preferably an isobutylene copolymer.
[0031] According to an embodiment of the present invention, in the (p-methyl)styrene-isobutylene copolymer, the molar content of (p-methyl)styrene is not more than 20 mol%, preferably 0.1-20 mol%, for example, 0.5 mol%, 1 mol%, 2 mol%, 3 mol%, 4 mol%, 5 mol%, 6 mol%, 7 mol%, 8 mol%, 9 mol%, 10 mol%, 15 mol%.
[0032] According to an embodiment of the present invention, the number average molecular weight of the thermoplastic elastomer is 2000 to 1000000, for example, 5000, 10000, 20000, 30000, 40000, 50000, 60000, 70000, 80000, 90000, 100000, 200000, 300000, 400000, 500000, 600000, 700000, 800000, 900000.
[0033] According to an embodiment of the present invention, in the composition, the content of the thermoplastic elastomer is, for example, 10 wt%, 20 wt%, 30 wt%, 40 wt%, 50 wt%, 60 wt%, or 70 wt%.
[0034] According to an embodiment of the present invention, the tackifier is selected from at least one of C5 petroleum resin, α-methylstyrene resin, C9 petroleum resin, aliphatic-modified aromatic C9 petroleum resin, phenol-modified aromatic resin, and C9 aromatic / aliphatic olefin derivative resins.
[0035] According to an embodiment of the present invention, the average molecular weight of the tackifier is 100-10000, for example, 1000, 2000, 3000, 4000, 5000, 6000, 7000, 8000, 9000.
[0036] According to an embodiment of the present invention, the softening point of the tackifier is 40-150°C, for example, 50°C, 60°C, 70°C, 80°C, 90°C, 100°C, 110°C, 120°C, 130°C, 140°C.
[0037] For example, the tackifier is, for example, C5 petroleum resin (ExxonMobil 1310LC).
[0038] According to an embodiment of the present invention, in the composition, the content of the tackifier is, for example, 10 wt%, 20 wt%, 30 wt%, 40 wt%, or 50 wt%.
[0039] According to an embodiment of the present invention, the composition may further include additives.
[0040] According to an embodiment of the present invention, the additive is selected from at least one of a filler, a light stabilizer, an antioxidant, a pigment, a flame retardant, and the like.
[0041] According to the embodiment of the present invention, the additives may be selected in a content known in the art, and are not specifically limited in the present invention.
[0042] According to an embodiment of the present invention, the composition further includes a cross-linking accelerator.
[0043] According to an embodiment of the present invention, the crosslinking accelerator is selected from an organic tin compound. Preferably, the organic tin compound can be selected from substances known in the art, such as at least one of dialkyltin dicarboxylate (dibutyltin dilaurate), tin carboxylate, and stannous carboxylate. Exemplarily, the stannous carboxylate is selected from stannous octoate and stannous acetate, preferably stannous octoate.
[0044] According to an embodiment of the present invention, in the composition, the content of the cross-linking accelerator is 0.001-20wt%, for example, 0.01wt%, 0.1wt%, 1wt%, 5wt%, 10wt%, 15wt%.
[0045] According to an embodiment of the present invention, the viscosity of the composition is 10,000-500,000 centipoise (150° C.).
[0046] The present invention also provides application of the sealant composition, which is used for manufacturing heat-insulating glass and solar photovoltaic.
[0047] According to an embodiment of the present invention, the sealant composition may be applied to the substrate in a manner known in the art, such as by an extruder, a hand spray gun, or the like.
[0048] According to an embodiment of the present invention, the substrate is selected from at least one of glass, polymer, metal, etc., preferably glass.
[0049] According to an embodiment of the present invention, when the sealant composition is coated, the coating temperature is 60°C-120°C, preferably 70-115°C, for example 80°C, 90°C, 100°C, 110°C.
[0050] According to an embodiment of the present invention, the sealant composition has an initial strength of not less than 27 kPa under coating conditions, such as 27-50 kPa, and for example 30 kPa or 40 kPa.
[0051] According to an embodiment of the present invention, the sealant composition is cured to obtain a sealant when exposed to room temperature (10-40°C, such as 25°C) and relative humidity of 10-90RH%. Preferably, the relative humidity is, for example, 30RH%, 50RH%, or 70RH%.
[0052] According to an embodiment of the present invention, the tensile strength of the sealant at room temperature (10-40° C., such as 25° C.) is 420-550 kPa, such as 450 kPa or 500 kPa.
[0053] According to an embodiment of the present invention, the sealant has a final lap shear strength of 200-800 kPa within 12 weeks after curing, for example, 300 kPa, 400 kPa, 500 kPa, 600 kPa, or 700 kPa.
[0054] According to an embodiment of the present invention, the Shore A hardness of the sealant is 20-75, for example, 30, 40, 50, 60, 70.
[0055] According to an embodiment of the present invention, the sealant provides good airtightness. Preferably, the water vapor transmission rate of the sealant (for example, when it is a 2 mm thick film) is not higher than 2.4 g / m 2 / day, for example, preferably 1.0 g / m 2 / day, 1.5g / m 2 / day, 1.9g / m 2 / day, 2.0g / m 2 / day, 2.1g / m 2 / day, 2.2g / m 2 / day, 2.3g / m 2 / sky.
[0056] According to an embodiment of the present invention, the sealant preferably passes the low temperature flexibility test of GB13477.7 at -30°C, -20°C and -10°C.
[0057] According to an embodiment of the present invention, the sealant passes a 60° C. creep resistance test.
[0058] According to an embodiment of the present invention, after the sealant is immersed in water, the glass bonding failure rate is less than 50%, preferably less than 5%, for example, 40%, 30%, 20%, 10%, 5%, 4%, 3%, 2%, or 1%.
[0059] Beneficial Effects
[0060] The sealant composition of the present invention has a suitable initial viscosity, is easy to apply, and is suitable for connecting glass to glass, polymer, metal and other substrates; achieves good bonding strength and air tightness, and has good solvent resistance, heat resistance and low temperature properties.
[0061] When the sealant composition of the present invention is used to manufacture insulating glass components and solar photovoltaics, it can not only bond the glass and its intermediate spacers to form a sealed hollow chamber, but also provide bonding and block the gas in the hollow chamber from leaving the hollow chamber. DETAILED DESCRIPTION
[0062] The technical scheme of the present invention will be further described in detail below in conjunction with specific embodiments. It should be understood that the following embodiments are only exemplary descriptions and explanations of the present invention and should not be construed as limiting the scope of protection of the present invention. All technologies implemented based on the above content of the present invention are included in the scope that the present invention is intended to protect.
[0063] Unless otherwise specified, the raw materials and reagents used in the following examples are commercially available or can be prepared by known methods.
[0064] Preparation Example 1
[0065] Preparation of p-methylstyrene-isobutylene copolymer:
[0066] The yellow polymer prepared in Example 1 of the patent document with the application number CN00804495.3 is silylated p-methylstyrene-isobutylene copolymer.
[0067] In the copolymer prepared as above, the molar content of trimethoxysilyl in each mole of the copolymer is 2.9 mol%, Mn=16100, and Mw / Mn=2.27.
[0068] Example 1
[0069] The preparation method of the sealant composition is as follows: preheat a mechanical stirring mixer equipped with a vacuum pump to 120°C, add 100g of butyl rubber (Zhejiang Xinhui Synthetic New Materials, IIR532); 100g of polyisobutylene (BASF, B12) and stir and mix for 20 minutes, then add 120g of amorphous polyalphaolefin (Evonik, VESTOPLAST508) and 120g of tackifying resin (ExxonMobil1310LC C5 petroleum resin) and continue to stir at 120°C for 15 minutes. Turn on the vacuum pump and continue to stir at 120°C for 30 minutes at a pressure of about 10KPa. Add 240g of silylated para-methylstyrene-isobutylene copolymer of Preparation Example 1 and continue to stir at this temperature for 30 minutes. Finally, add 0.15g of dibutyltin dilaurate and continue to mix and stir under vacuum for 15 minutes to obtain the sealant composition.
[0070] Example 2
[0071] The preparation method of the sealant composition is as described in Example 1, and the components and their amounts are as described in Table 1 to prepare the sealant composition of Example 2.
[0072] Comparative Example 1
[0073] The preparation method of the sealant composition in this comparative example refers to Example 1, and the components and their amounts refer to Table 1 to prepare the sealant composition of Comparative Example 1.
[0074] Comparative Example 2
[0075] This comparative example is basically the same as Example 1, except that the silylated para-toluene-isobutylene copolymer of Preparation Example 1 is replaced with a silylated amorphous poly-alpha-olefin (Evonik, VSTOPLAST206) to prepare the sealant composition of this comparative example.
[0076] Test Case
[0077] The sealant compositions of the above embodiments and comparative examples were taken and the test results such as lap shear strength, hardness, low temperature flexibility (-10°C, -20°C, -30°C), glass bonding failure rate and creep resistance were measured according to the following test methods, and the results are recorded in Table 1.
[0078] In the following test method, room temperature specifically refers to a temperature of 25° C. and a relative humidity of 50%.
[0079] (1) Lap shear strength
[0080] Refer to MH / T 6099-2013 Sealant Lap Shear Strength Test Method to determine the lap shear strength:
[0081] (1) The test sample preparation method is as follows: the sealant composition is made into a 25 mm × 25 mm, 2 mm thick film, the film is placed on a 100 mm × 25 mm aluminum sheet, a 25 mm × 75 mm glass sheet is placed on top of the film, and the glass sheet and the aluminum sheet are pressed hard to bond, and then heated at 120°C for 10 min to obtain a test sample.
[0082] (2) Test the initial lap shear strength of the sample within 1-2 minutes after obtaining it;
[0083] (3) After the test samples were placed for 12 weeks, the final lap shear strength was tested.
[0084] (II) Water vapor transmission rate test
[0085] The test was conducted with reference to the cup method in GB / T 1037-2021 Test method for water vapor permeability of plastic film and sheet. The sealant composition was made into a film with a thickness of 2 mm and heated at 120°C for 10 min to obtain a sample. The permeability coefficient of the sample at 37°C and 90% relative humidity was measured using an infrared sensor method moisture permeability meter (LabThink C390H), which is the water vapor permeability.
[0086] (III) Hardness
[0087] The test was conducted using a Shore A hardness tester. The 2 mm thick film prepared in the above method (I) was used. The initial hardness was measured after heating at 120°C for 10 min. The final hardness was measured after the sample was left for 12 weeks.
[0088] (IV) Low temperature flexibility test
[0089] The test was conducted in accordance with GB / T 13477.7-2002 “Test methods for building sealing materials Part 7: Test for low temperature flexibility”.
[0090] (V) Glass bonding failure rate test
[0091] A 50 mm × 40 mm spacer was placed between two pieces of 25 mm × 80 mm glass in a fixture, and the fixture was clamped to form a channel between the two pieces of glass due to the spacer; the sealant composition was spread with a spatula to fill the channel between the two pieces of glass to obtain a sample, and then the sample was placed in an oven at 140°C and heated for 10 minutes, taken out and cooled overnight to obtain a glass connector sample.
[0092] After the glass connector samples were treated under the following conditions (1)-(3), the glass bonding failure rate of the samples was:
[0093] (1) Place at room temperature for one week;
[0094] (2) Soak in deionized water for one week, take out and dry (wipe dry or air dry) before testing;
[0095] (3) Place at 60°C, 100% relative humidity for one week.
[0096] (VI) Creep resistance
[0097] (1) The sample preparation method is as follows: the above-mentioned sealant composition is made into a 25 mm × 25 mm film with a thickness of 2 mm, and the films are placed on a 100 mm × 25 mm aluminum sheet, and a 25 mm × 80 mm glass sheet is placed on top of the film. Press hard to bond them together, place them in an oven at 120°C and heat them for 10 minutes. After leaving them at room temperature for 4 weeks, the samples are obtained.
[0098] (2) Test: Hang a 500g load on one end of the sample and place it in a 60℃ oven. Record the failure time. If there is no failure after 7 days, it is considered to have passed.
[0099] Table 1
[0100]
[0101]
[0102] From the experimental results, the sealant composition of the present invention not only has a suitable initial viscosity and is convenient for coating, but also has excellent wet strength after curing, good water resistance, heat resistance and low temperature properties, and high bonding ability with the glass substrate. When used to prepare insulating glass, it can not only provide strong bonding force, but also block the gas in the hollow cavity from leaving the hollow cavity.
[0103] The above is a description of the exemplary embodiments of the present invention. However, the protection scope of the present application is not limited to the above embodiments. Any modification, equivalent substitution, improvement, etc. made by those skilled in the art within the spirit and principle of the present invention shall be included in the protection scope of the present invention.
Claims
1. A sealant composition, characterized in that: The composition comprises at least: Silylated (p-methyl) styrene-isobutylene copolymer 5-80wt%; Thermoplastic elastomer 1-75wt%; and Tackifier 5-60wt%.
2. The composition according to claim 1, characterized in that The composition also contains 5-50 wt% of amorphous poly-α-olefin. Preferably, the grafting rate of silane groups in the silylated (p-methyl)styrene-isobutylene copolymer is 0.1 to 20 mol%. Preferably, the silylated (p-methyl)styrene-isobutylene copolymer is moisture curable. Preferably, the silylated (p-methyl)styrene-isobutylene copolymer is selected from at least one of an isobutylene copolymer and a reactant of a silane of the general formula RR′SiY2; In the general formula of the silane RR′SiY2, R is selected from a monovalent olefinic unsaturated hydrocarbon or a hydrocarbyl group that can react with a free radical point generated on the main chain of the isobutylene copolymer; when R is selected from a hydrocarbyl group, it is not hydrolyzable; R′ is selected from alkyl, aryl or Y; Y is selected from hydrolyzable organic groups.
3. The composition according to claim 1 or 2, characterized in that In the general formula, R is selected from vinyl, allyl, butenyl, 4-pentenyl, 5-hexenyl, cyclohexenyl or cyclopentadienyl. Preferably, in the general formula, Y is selected from at least one or two or more of an alkoxy group, an acyloxy group, an oximo group, and a substituted amino group. Preferably, in the general formula, R′ represents an alkyl group, an aryl group or Y. Preferably, in the general formula of the silane, R is selected from a vinyl group, R′ is selected from a methyl group or a Y group, and Y is selected from an alkoxy group. Preferably, the silane is selected from at least one of vinyltriethoxysilane, vinyltrimethoxysilane and methylvinyldimethoxysilane. Preferably, the number average molecular weight of the silylated (p-methyl)styrene-isobutylene copolymer is 2,000-1,000,000.
4. The composition according to any one of claims 1 to 3, characterized in that The amorphous poly-α-olefin refers to an amorphous homopolymer and / or copolymer of monomers such as ethylene, propylene, 1-butene, 1-pentene, 3-methyl-1-butene, 1-hexene, 3-methyl-1-pentene, 4-methyl-1-pentene, 3-ethyl-1-pentene, 1-octene, 1-decene, 1-undecene, etc. Preferably, the amorphous poly-α-olefin is selected from at least one of random polypropylene, propylene / ethylene amorphous copolymer, propylene / 1-butene amorphous copolymer, and ethylene / propylene / 1-butene terpolymer. Preferably, the number average molecular weight of the amorphous poly-α-olefin is 5,000-100,000.
5. The composition according to any one of claims 1 to 4, characterized in that The thermoplastic elastomer is selected from at least one of polyisobutylene, isobutylene copolymer, ethylene-propylene rubber, butadiene-styrene block copolymer, isoprene-styrene block copolymer, ethylene vinyl acetate, random polypropylene, and ethylene acrylate (methyl) copolymer. Preferably, in the (p-methyl)styrene-isobutylene copolymer, the molar content of (p-methyl)styrene is not more than 20 mol %. Preferably, the number average molecular weight of the thermoplastic elastomer is 2,000 to 1,000,000.
6. The composition according to any one of claims 1 to 5, characterized in that The tackifier is selected from at least one of C5 petroleum resin, α-methylstyrene resin, C9 petroleum resin, aliphatic-modified aromatic C9 petroleum resin, phenol-modified aromatic resin, and C9 aromatic / aliphatic olefin derivative resins. Preferably, the average molecular weight of the tackifier is 100-10000. Preferably, the softening point of the tackifier is 40-150°C.
7. The composition according to any one of claims 1 to 6, characterized in that The composition also includes additives. Preferably, the additive is selected from at least one of a filler, a light stabilizer, an antioxidant, a pigment, and a flame retardant. Preferably, the composition further comprises a cross-linking accelerator. Preferably, the cross-linking accelerator is selected from organotin compounds. Preferably, in the composition, the content of the cross-linking accelerator is 0.001-20 wt %. Preferably, the viscosity of the composition is 10,000-500,000 centipoise.
8. Use of the sealant composition according to any one of claims 1 to 7 for manufacturing heat-insulating glass and solar photovoltaics.
9. The use according to claim 8, characterized in that: The sealant composition is applied to a substrate. Preferably, the substrate is selected from at least one of glass, polymer and metal. Preferably, when the sealant composition is applied, the coating temperature is 60°C-120°C. Preferably, the sealant composition has an initial strength of not less than 27 kPa under coating conditions. Preferably, the sealant composition is cured to obtain a sealant when exposed to room temperature and a relative humidity of 10-90 RH%.
10. The use according to claim 8 or 9, characterized in that: The tensile strength of the sealant at room temperature is 420-550 kPa. Preferably, the sealant has a final lap shear strength of 200-800 kPa within 12 weeks after curing. Preferably, the sealant has a Shore A hardness of 20-75. Preferably, the sealant provides good airtightness. Preferably, the sealant passes the low temperature flexibility test of GB 13477.7 at -30°C, -20°C and -10°C. Preferably, the sealant passes a 60°C creep resistance test. Preferably, after the sealant is immersed in water, the glass bonding failure rate is less than 50%.
Citation Information
Patent Citations
Silane grafted copolymers of an isomonoolefin and vinyl aromatic monomer
CN1342176A